Pathogenicity and transmissibility studies on live attenuated duck enteritis virus vaccine in non-target species - Kong, Jie; Feng, Keyu; Zhao, Qiqi; Chen, Yazheng; Wang, Jinfeng; Chen, Sheng; Shao, Guanming; Liao, Liqin; Li, Yajuan; Xie, Zi; Zhang, Xinheng; Xie, Qingmei (Frontiers in Microbiology, 2022)
In the second half of 2021, a highly pathogenic case occurred in a mixed chicken and duck family farm in Guangdong, China. After the duck flocks were immunized with live attenuated duck enteritis virus vaccine (live attenuated DEV vaccine), the chickens of the same farm showed clinical symptoms similar to duck enteritis, such as pericardial effusion, hepatic hemorrhagic spots, kidney enlargement, intestinal bleeding, with mass mortality. The infection model of target animal tested, as well as the non-target species, were established according to the risk of live attenuated DEV vaccine and transmission in chickens. Live attenuated DEV vaccine was initially replicated in host animals, released the virus, and effectively colonized in the common environment, according to birds challenged experiments. There was evidence to suggest the mode of transmission of duck enteritis virus, horizontal transmission are the main routes of DEV transmission. In addition, high levels of virus titer were detected in chicken embryos and different tissue of SPF chickens. Different degrees of pathological damage occurred in the tissue of chickens. After the SPF chickens were inoculated with live attenuated DEV vaccine, different degrees of virulence were exhibited, pointing to a potential risk to other domestic bird species.